Gender and sex bias in prevention and clinical treatment of women’s chronic pain: hypotheses of a curriculum development - Moretti, Chiara; De Luca, Enrico; D’Apice, Clelia; Artioli, Giovanna; Sarli, Leopoldo; Bonacaro, Antonio (Frontiers in Medicine, 2023)
This manuscript focuses on the role that undergraduate medical education may play in tackling gender bias in medical practice with reference to preventing and managing chronic pain in women in a non-biomedical perspective. The paper proposes an innovative curriculum development approach to be implemented throughout all years of study in medical programs. This novel strategy could be used to cross-contaminate all other healthcare practitioners’ university programs and to stimulate an interprofessional debate aiming at fostering inclusiveness and equality of opportunities in medicine and allied health sciences.